2016
DOI: 10.1177/1479972316660977
|View full text |Cite
|
Sign up to set email alerts
|

Living with asthma and chronic obstructive airways disease: Using technology to support self-management – An overview

Abstract: Long-term respiratory conditions such as asthma and chronic obstructive pulmonary disease (COPD) are common, and cause high levels of morbidity and mortality. Supporting self-management is advocated for both asthma and increasingly so for COPD, and there is growing interest in the potential role of a range of new technologies, such as smartphone apps, the web or telehealth to facilitate and promote self-management in these conditions. Treatment goals for both asthma and COPD include aiming to control symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 91 publications
(139 reference statements)
0
32
0
3
Order By: Relevance
“…These findings challenge the potential efficiency, efficacy and benefit of the widespread deployment of the telehealth for patients with COPD at present. 5 Although the deployment of telehealth may be better served by the use of portable technologies, such as smart phones, 7 we did not measure this in the current study but hypothesise that ownership may be limited. Of interest, and probably reflecting the low socio-economic standing of these COPD patients, the access to computer and internet technology in this cohort is markedly lower than the general elderly population within the United Kingdom.…”
mentioning
confidence: 92%
“…These findings challenge the potential efficiency, efficacy and benefit of the widespread deployment of the telehealth for patients with COPD at present. 5 Although the deployment of telehealth may be better served by the use of portable technologies, such as smart phones, 7 we did not measure this in the current study but hypothesise that ownership may be limited. Of interest, and probably reflecting the low socio-economic standing of these COPD patients, the access to computer and internet technology in this cohort is markedly lower than the general elderly population within the United Kingdom.…”
mentioning
confidence: 92%
“…The potential for digital technology to help people with COPD to self-manage their condition is increasingly being investigated [ 19 , 20 ] and advocated in the NHS [ 10 , 21 ]. Bartlett et al [ 22 ] demonstrated that people with COPD find support with a primary task, and dialog support (eg, through feedback), to be persuasive technological strategies to help increase their levels of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although mHealth tools represent a promising means to encourage greater self-management of COPD, findings from a systematic review in this field were inconclusive owing to a high risk of bias in the included studies, thus indicating the need for more research [ 19 ]. Digital health interventions should be evidence based, person based, and robustly evaluated, with considerations given to future implementation of the intervention at an early stage of its development [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…We are witnessing a rapid shift towards more sophisticated mobile health interventions for respiratory disease management, including eHealth 23 and mobile-based apps that require further testing but also development and maintenance. SMS reminders are cheap, use existing infrastructure and are acceptable to patients.…”
Section: Resultsmentioning
confidence: 99%